2022
DOI: 10.1177/03635465221097410
|View full text |Cite
|
Sign up to set email alerts
|

Results of Arthroscopic Revision Rotator Cuff Repair for Failed Open or Arthroscopic Repair: A Prospective Multicenter Study on 100 Cases

Abstract: Background: Retears after rotator cuff repair (RCR) have been associated with poor clinical results. Meaningful data regarding the role of arthroscopic revision RCR are sparse thus far. Purpose/Hypothesis: To investigate results after arthroscopic revision RCR. We hypothesized that (1) arthroscopic revision RCR would lead to improved outcomes, (2) the clinical results would be dependent on tendon integrity and (3) tear pattern, tendon involvement, and repair technique would influence clinical and structural re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…5,8,13-15,18,19,21,29 The mean ASES score was 75.0 ± 18.3 at a mean follow-up of 44.4 ± 20.4 months (range, 12-165 months). Additionally, the mean Subjective Shoulder Value, Constant score, Simple Shoulder Test, University of California Los Angeles (UCLA) shoulder score, and Single Assessment Numeric Evaluation were reported at final follow-up in 3, 1,9,29 7, 1,8,9,13,18,21,26 4, 13,19,21,26 6, 4,5,8,15,16,29 and 3 15,19,21 studies, respectively, and were 72.5 ± 12.7, 67.4 ± 16.6, 7.8 ± 7.0, 27.1 ± 5.4, and 71.5 ± 20.2, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,13-15,18,19,21,29 The mean ASES score was 75.0 ± 18.3 at a mean follow-up of 44.4 ± 20.4 months (range, 12-165 months). Additionally, the mean Subjective Shoulder Value, Constant score, Simple Shoulder Test, University of California Los Angeles (UCLA) shoulder score, and Single Assessment Numeric Evaluation were reported at final follow-up in 3, 1,9,29 7, 1,8,9,13,18,21,26 4, 13,19,21,26 6, 4,5,8,15,16,29 and 3 15,19,21 studies, respectively, and were 72.5 ± 12.7, 67.4 ± 16.6, 7.8 ± 7.0, 27.1 ± 5.4, and 71.5 ± 20.2, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 included studies, 10 (n = 526) 1,4,5,9,[13][14][15]18,23,29 reported on the rate of recurrent tears at final followup. The overall rate of retears was 25.3% (133/526).…”
Section: Recurrent Tears Complications and Reoperationsmentioning
confidence: 99%
“…11,24 A single row repair often has to be performed, as tendon loss and repair tension may not allow for a double row construct. 19 Outcome studies have demonstrated that after revision repair, patients have improvement in pain and function, [27][28][29][30][31][32][33] and increases in active shoulder forward elevation and external rotation. 28 However, the complication rate is 2-fold compared with a primary repair, with a retear rate of 32.6% to 87% [30][31][32][33][34] and a reoperation rate of 12.6% to 34.7%.…”
Section: Revision Rotator Cuff Repairmentioning
confidence: 99%
“…19 Outcome studies have demonstrated that after revision repair, patients have improvement in pain and function, [27][28][29][30][31][32][33] and increases in active shoulder forward elevation and external rotation. 28 However, the complication rate is 2-fold compared with a primary repair, with a retear rate of 32.6% to 87% [30][31][32][33][34] and a reoperation rate of 12.6% to 34.7%. 31,32 As such, augmentation techniques to optimize healing of the revision repair are becoming increasingly popular.…”
Section: Revision Rotator Cuff Repairmentioning
confidence: 99%
See 1 more Smart Citation